Scientific Society for the Study of Vlach Culture - (:unkn) unknown (My University, 2026)
The primary purpose of the Scientific Society for the Study of Vlach Culture, is the research, recording and study of all forms of Vlach culture with an emphasis on the language and its geographical varieties